Implementasi Pendekatan Balanced Scorecard Sebagai Tolak Ukur Kinerja Perusahaan pada PT. PLN ULP Lawang - Lingga Aprilia Putri Yuana; Dwiyani Sudaryanti; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2023)
Performance is the result of work in quality and quantity that can be achieved by an employee in carrying out his main duties and functions as an employee in accordance with the responsibilities given or entrusted. The more rapid development, especially in the industrial sector, both home industries and large industries, causes the need for electricity supply to increase. This is a challenge for PT. PLN (Persero) ULP Lawang to improve performance in all aspects using a method that has an overall measurement variable, namely the Balanced scorecard. The purpose of this study was to determine the performance of PLN ULP Lawang as measured by using the Balanced scorecard. By using a qualitative method which is a research procedure that produces data in the form of written or spoken words from the observed behavior. Based on the results of the analysis of the performance measurement of PLN ULP Lawang using a Balanced scorecard, each perspective is said to be relatively good.Keywords: Balanced scorecard, performance, perspective, PT PLN (Persero) ULP Lawang